In-Situ Testing Technology and Its Application for External Water Pressure in Deep-Buried Tunnels Based on Directional Drilling - FAN Shi-jie, WANG Zi-zhong, LI Long, CHEN Ying, YU Lei, MAI Gao-fei, WANG Bo, WANG Jun-chao (长江科学院院报)
[Objective] External water pressure is a critical parameter in the construction design of deep-buried tunnels. During the early investigation stage, it is difficult to obtain this parameter through traditional vertical borehole exploration. In engineering practice, the reduction coefficient method is generally used to estimate the external water pressure of tunnels. To achieve more accurate evaluation, a testing technology for external water pressure in deep-buried tunnels was proposed based on directional drilling. An in-situ testing system for external water pressure, with storage-type pressure sensors as its core, was developed and applied to the granite section of the Erlangshan Tunnel in Dadu River to Minjiang River Water Diversion Project. [Methods] Full-depth testing of the external water pressure in the tunnel was conducted using directional drilling to reveal the distribution of external water pressure along the axis of the deep-buried tunnel. The calculated values obtained from the reduction coefficient method were analyzed and compared. [Results] Based on Pearson correlation analysis, the measured external water pressure exhibited an extremely strong correlation with the total width of the fracture-intensive zone (r=0.85), a strong correlation with rock mass permeability (r=0.64), and a weak correlation with the burial depth of the test section (r=0.16). The measured external water pressure was 20.47% to 42.17% higher than that calculated by the reduction coefficient method. [Conclusions] Compared with the traditional reduction coefficient method, this study analyzes the external water pressure of the tunnel using water pressure values obtained from segmented and continuous measurements in a natural three-dimensional groundwater seepage field through in-situ testing methods, providing more reliable analysis of tunnel external water pressure in engineering practice. This study provides an in-situ quantitative testing method for external water pressure testing during the early investigation stage of tunnels, thereby offering a more scientific reference for the design, construction, and operational safety of deep-buried tunnels.